Pseudomonas aeruginosa Trent and zinc homeostasis. Issue 16 (20th July 2017) - Davies, Corey B.; Harrison, Mark D.; Huygens, Flavia
Abstract: Pseudomonas aeruginosa is a Gram-negative pathogen and the major cause of mortality in patients with cystic fibrosis. The mechanisms that P. aeruginosa strains use to regulate intracellular zinc have an effect on infection, antibiotic resistance and the propensity to form biofilms. However, zinc homeostasis in P. aeruginosa strains of variable infectivity has not been compared. In this study, zinc homeostasis in P. aeruginosa Trent, a highly infectious clinical strain, was compared to that of a laboratory P. aeruginosa strain, ATCC27853. Trent was able to tolerate higher concentrations of additional zinc in rich media than ATCC27853. Further, pre-adaptation to additional zinc enhanced the growth of Trent at non-inhibitory concentrations but the impact of pre-adaption on the growth of ATCC27853 under the same conditions was minimal. The results establish clear differences in zinc-induced responses in Trent and ATCC27853, and how zinc homeostasis can be a promising target for the development of novel antimicrobial strategies for P. aeruginosa infection in cystic fibrosis patients. Abstract : Pseudomonas aeruginosa Trent strain responds differently to a laboratory strain in media containing elevated zinc.